PROFIL KONDISI FISIK WUSHU SANDA PPLOP JAWA TENGAH TAHUN 2023 - Muhamad Fadly Ulummudin; Siti Baitul Mukarrohmah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Physical condition is really needed by athletes as evaluation material to find out how far the goals achieved from the results of their training. The aim of this research is to determine the Physical Condition Profile of Wushu Sanda PPLOP Central Java in 2023. The method used is descriptive quantitative. The sampling technique uses total sampling because the population is less than 30 people. The data collection technique uses physical condition measurement tests. Data analysis used descriptive statistics with SPSS version 25. The results showed that the physical condition in each test for 30 meter running speed was in the very good category, abdominal muscle strength in the good category, arm muscle strength in the medium category, leg muscle strength in the medium category, flexibility in the very good category, agility in the very good category. , endurance in the poor category, shoulder muscle strength in the very good category, 300 meter running speed in the medium category, and arm muscle strength in the very good category. The conclusion of this research is that the active physical condition profile of Wushu Sanda PPLOP Central Java in 2023 based on the t score in the "Very Poor" category is 14.29%, the "Poor" category is 14.29%, "Fair" is 42.86%, and the "Good" category was 28.57%. Meanwhile, based on the average value of 500.05, the active physical condition profile of Wushu Sanda PPLOP Central Java in 2023 is included in the "sufficient" category.